Between Stillness and Motion Film, Photography, Algorithms - Røssaak, Eivind (Film Culture in Transition, 2011)
New technological media such as film, photography and computers have altered the way we perceive possible relations between stillness and motion in the visual arts. Traditionally, cinema theory saw cinema and especially the 'illusion of motion' as part of the ideological swindle of the basic cinematic apparatus. This collection of essays by acclaimed international scholars including Tom Gunning, Thomas Elsaesser, Mark B.N. Hansen, George Baker, Ina Blom and Christa Blümlinger, starts out from a different premise to analyse stillness and motion as part of a larger ecology of images and media. They argue that the strategic uses of stillness and motion in art and entertainment since the 1850s illuminate and renegotiate urgent issues within both aesthetics, film, art and media history on the one hand, and, on the other, new perspectives on affects, memories and the contemporary patterns of communication and image circulation.